Characterization of foxl2, sox9, and wt1a genes and their expression pattern as putative targets for sex identification in Astronotus ocellatus (Agassiz, 1831) - Ferreira Souza de Carvalho, Aline; Silvestre de Azevedo Martins, Moises; Marques Paiva, Isadora; Gilmar da Silva Souza, José; Paula Peconick, Ana; V. Baanante, Isabel; Metón, Isidoro; Franco Carneiro, William; David Solis Murgas, Luis (Archives of Veterinary Science, 2025)
Abstract: Using molecular markers is an effective method for sex identification in fish. In this regard, autosomal genes related to sex determination and differentiation may be of great interest. This study aimed to evaluate the expression pattern of Foxl2, Sox9, and Wt1a as molecular markers for sex identification in Oscar (Astronotus ocellatus). Molecular characterization and gene expression profiles for forkhead box l2 (Foxl2), SRY-box 9 (Sox9), and Wilm’s tumor suppressor gene (Wt1a) were performed in male and female gonads. After euthanasia, histological and molecular analyses were conducted using ovarian and testis fragments of adult A. ocellatus. Histology was used for sex confirmation. The isolation of partial cDNA sequences encoding Foxl2, Sox9, and Wt1a from A. ocellatus was obtained by PCR using primers designed from conserved regions of the corresponding coding-domain sequence in other species. Sequencing of A. ocellatus Foxl2, Sox9, and Wt1a cDNA fragments allowed us to perform RT-qPCR assays in male and female gonadal tissue to analyze the gene expression profile. RT-qPCR revealed markedly gender-influenced gene expression patterns for all target genes. Foxl2 mRNA levels were significantly higher in the ovary than in the testes. At the same time, Sox9 and Wt1a were upregulated considerably, and mRNA levels for Sox9 and Wt1a were 8- and 9-fold higher in the testis compared to the ovary. Our findings indicate that Foxl2 expression may serve as a molecular marker for the identification of males. At the same time, the genes Sox9 and Wt1a are effective in identifying females in A. ocellatus gonads up to 12 months of age.